State of seagrass in two Northern Key beaches, before and after hurricane Irma passing through the Ciego de Ávila province, Cuba - Cruz-Pérez, Claudia M. (2019)
Seagrass meadows are considered one of the most valuable ecosystems of the biosphere. In the Northern Keys of the Ciego de Ávila province, seagrass showed structural and composition damages due to hurricane Irma’s impact. The state of seagrass meadows was evaluated at Las Coloradas and El Paso beaches in November 2017 after the hurricane, based on a characterization conducted in June 2017. For both samples, three 50 m transects were located parallel to the coast.  Along each transect, 12 0.25 m2 frames were placed. The predominant marine angiosperm was T. testudinum, and S. filiforme at a lower scale. A total of 25 macroalgae species and four stony coral species were identified. The most predominant invertebrate species found were O. reticulatus and L. gigas, while the most abundant fish species were H. bivittatus and G. cinereus. In November, S. filiforme disappeared, the diversity of invertebrates associated with seagrasses declined, and no ichthyofauna was recorded. Hurricane Irma was an extreme meteorological event that changed the composition and structure of seagrass meadows at Las Coloradas and El Paso beaches, because of its impact in the decrease of the relative abundance and shoot density of T. testudinum, the height of dossal, and the epiphytism percentage of the species, as well as the decrease in seagrass fauna. Seagrass sites must continue to be monitored to study their level of recovery over time.